Economic order quantity for growing items in the presence of mortality - Pourmohammadzia, Nadia (Journal of Supply Chain Management Science, 2022)
Growth depicts the behavior of a class of inventories whose weight and size increase during their storage. Although the phenomenon is fundamental in the food industry, it still faces a lack of academic heed. Our research sheds new light on this area by illustrating the inventory system of a rearing farm that breeds fast-growing newborn animals (like broiler chickens) and finally slaughters them. The items are prone to different diseases during their growth which can lead to their death. This is modeled by applying a mortality rate that can be controlled by investing in preventive practices. The slaughtered items (such as chicken meat) that fall into the category of deteriorating inventory are quality controlled and exploited to satisfy demand. An analytic solution approach is developed to derive the optimal order quantity of newborn animals, their growth period, and action level for preventive practices. Experimental results show that choosing a hatchery with the best purchasing cost should be the first priority of the system to manage its costs. It is also depicted that the breeding period is not influenced by all input parameters of the model, and the nature of the items plays a key role in this regard.